Chemical pollution: A growing peril and potential catastrophic risk to humanity - Naidu, Ravi; Biswas, Bhabananda; Willett, Ian R.; Cribb, Julian; Kumar Singh, Brajesh; Paul Nathanail, C.; Coulon, Frederic; Semple, Kirk T.; Jones, Kevin C.; Barclay, Adam; Aitken, Robert John (Environment international, 2021)
[Display omitted] •The global picture of chemical pollution in the environment is often fragmented.•This perspective highlights global picture of pollution regarding catastrophic risk.•Exposure related impact on fertility, cognition and food safety are discussed.•Prioritised strategies for curbing chemical dispersal are recommended. Anthropogenic chemical pollution has the potential to pose one of the largest environmental threats to humanity, but global understanding of the issue remains fragmented. This article presents a comprehensive perspective of the threat of chemical pollution to humanity, emphasising male fertility, cognitive health and food security. There are serious gaps in our understanding of the scale of the threat and the risks posed by the dispersal, mixture and recombination of chemicals in the wider environment. Although some pollution control measures exist they are often not being adopted at the rate needed to avoid chronic and acute effects on human health now and in coming decades. There is an urgent need for enhanced global awareness and scientific scrutiny of the overall scale of risk posed by chemical usage, dispersal and disposal.